Global Digital Trade Regulation: An International Law Perspective on Cross-Border Data Flows and Privacy Standards - Fahriawan, Hendra; Hasibuan, Ibnu Habibi; Rahmawati, Amanda (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Digital trade has become the backbone of a data-driven economy; however, no international legal framework exists at present for the regulation of cross-border data flows in any fair and effective manner. This research is interested in an analysis of international digital trade regulations under the architectures of international law, particularly in tension between economic liberalization and the protections provided by privacy laws. The research utilizes a normative qualitative method through content analysis of 27 multilateral, regional, and national legal documents in conjunction with a literature review and comparative analysis. The study reveals a significant extent of regulatory fragmentation across jurisdictions like the European Union with the GDPR, China's PIPL, and a sectoral system in the United States. Such fragmentation is reflective of differing foundational legal values acting in the attorney space, leading to both legal uncertainty and dual compliance costs, as well as potential conflicts between states' regulations. The current study presents a normative model based on three principles of international law: non-discrimination, sovereignty of states, and protection of human rights, for creating an inclusive global legal framework. In theory, this study serves an important purpose of extending the discourses of international law and digital geopolitics. In practice, it will lay down a roadmap for a global policy addressing regulatory conflict resolution and support participation by developing countries, whereas issues of digital trade can gain much from multilateral cooperation. Thus, the proposed framework will not only bridge theoretical gaps but also give precise guidance for the establishment of a fair, representative, and sustainable global policy architecture.